(untitled) - Rivera, Rawlinson (Indianapolis, Ind., 2008)
Streamline your exam preparation with this two-in-one guide that covers both of the new MCITP: Enterprise Messaging Administrator exams: Designing Messaging Solutions with Microsoft Exchange Server 2007 (exam 70-237) and Deploying Messaging Solutions with Microsoft Exchange Server 2007 (exam 70-238). If you're planning an upgrade to Exchange Server 2007 or are currently designing and deploying messaging solutions with it, this book is the practical tool you need to prepare for certification and build job skills.
Keywords: Microsoft Exchange server,Client/server computing,Telecommunication; Message processing